Study on physiological character of root system between maize genotypes with different tolerance to drought - LIU Sheng-qun; SONG Feng-bin (浙江大学学报. 农业与生命科学版, 2007)
Physiological functions between two maize genotypes of Yedan-13 (drought tolerance) and Danyu-13 (non-drought tolerance) with different tolerance to drought in the field condition were investigated. The root distribution, water retention capacity, absorbent area, soluble sugar content, reductive sugar content and nitrate reductase activity (NRA) of two maize genotypes at different growing periods including seedling, elongation, booting and filling stages were measured. The results showed that the dry weight and oxidizing ability of roots below 21 cm underground depth of Yedan -13 were higher than that of Danyu-13 at mostly significant difference level (P<0.01). And the water retention capacity, soluble sugar content, reductive sugar content and nitrate reductase activity of Yedan-13 were also significantly higher than that of Danyu-13 (P<0.05). However, there were no significant differences in total absorption area and active absorption area of root between two genotypes (P>0.05). These results indicated that the biological water-saving and water retention capacity of root has an important effect on the drought resistance of maize.